APLIKASI LOCATION QUATION DAN SHIFTSHARE ANALYSIS UNTUK MENGETAHUI POTENSI DAN ARAH INVESTASI PEMBANGUNAN DAERAH (Suatu Studi di Kota Payakumbuh) - Chan, Syafrizal (Program Studi Magister Ilmu Ekonomi, 2014)
Investmentplays a veryimportantto supporeconomic growth, create jobs, reduce poverty, andincreaseper capita income. Because of the potentia landdirection oftheinvestment must be knownandbe done with the right target. This study is to know the reality, potential anddirection of future investment Kota Payakumbuh by applying a Location Quation and Shift Share Analysis. From theanalysis conducted, it turns Kota Payakumbuh very attractive a san investment destination, because there area variety of potential business fieldof interestand benefit to be developed in the future. The main priority of investment is the field of process ing industry business, trade, hotels and restaurants, as well asservices, especially formicro, small, and medium business, as well as large businesses. Conditions in the are aincluded into the category of safe and comfortable, and there is nothreatf earth quakes and tsunamis as other coastala reason the western shoreof Sumatra. Very strategic location of thearealed to severalcities in the Province of Riauand West Sumatra. The local governmenthas also setup the necessary in frastructure, and there are variousÂ regulationst oen sure business certainty. Keywords: Potential Business, Directionof Investment, Opportunities, Strategic Issues, and Competitiveness.